Efficacy and Safety of Masitinib in Progressive Forms of Multiple Sclerosis: A Randomized, Phase 3, Clinical Trial. Issue 3 (21st May 2022) - Vermersch, Patrick; Brieva-Ruiz, Luis; Fox, Robert J.; Paul, Friedemann; Ramio-Torrenta, Lluis; Schwab, Matthias; Moussy, Alain; Mansfield, Colin; Hermine, Olivier; Maciejowski, Maciej; ,
Abstract : Background and Objectives: Masitinib is a selective tyrosine kinase inhibitor, targeting innate immune cells (mast cells and microglia) that are involved in the pathophysiology of progressive multiple sclerosis (MS). Study AB07002 assessed oral masitinib in patients with progressive MS who were progressing but not clinically active. Methods: This randomized, double-blind, 2 parallel-group, placebo-controlled trial assessing 2 dose levels of masitinib vs equivalent placebo was conducted at 116 hospital clinics and specialized MS centers in 20 countries. Randomization (2:1) with minimization was performed centrally using an automated system. Patients, physicians, and outcome assessors remained masked to treatment group allocation. Patients with primary progressive MS (PPMS) or nonactive secondary progressive MS (nSPMS) without relapse for ≥2 years, aged 18–75 years, with baseline Expanded Disability Status Scale (EDSS) 2.0–6.0, and regardless of time from onset were treated for 96 weeks. The primary end point was overall EDSS change from baseline using repeated measures (generalized estimating equation, timeframe W12–W96, measured every 12 weeks), with positive values indicating increased clinical deterioration. Efficacy and safety were assessed in all randomly assigned and treated patients. Results: A total of 611 patients were randomized; 301 in the masitinib 4.5 mg/kg/d parallel group and 310 in the uptitrated masitinib 6.0 mg/kg/d parallel group. Masitinib (4.5 mg/kg/d) (n = 199) showed significant benefit over placebo (n = 101) according to the primary end point, 0.001 vs 0.098, respectively, with a between-group difference of −0.097 (97% CI −0.192 to −0.002); p = 0.0256. Safety was consistent with masitinib's known profile (diarrhea, nausea, rash, and hematologic events), with no elevated risk of infection. Efficacy results from the independent uptitrated masitinib 6.0 mg/kg/d parallel group were inconclusive, and no new safety signal was observed. Discussion: Masitinib (4.5 mg/kg/d) can benefit people with PPMS and nSPMS. A confirmatory phase 3 study will be initiated to substantiate these data. Trial Registration Information: The first participant was randomized to study AB07002 on August 25, 2011. The trial was registered with the European Clinical Trials Database (#EudraCT 2010-021219-17) on July 1, 2011 (clinicaltrialsregister.eu/ctr-search/trial/2010-021219-17/ES ) and with ClinicalTrials.gov (#NCT01433497) on September 14, 2011 (clinicaltrials.gov/ct2/show/NCT01433497 ). Classification of Evidence: This study provides Class II evidence that masitinib 4.5 mg/kg/d decreased progression of disability, measured by the EDSS, in adults with PPMS or patients with nSPMS (with no exacerbations in the last 2 years).